The weekend effect in status epilepticus: a national cohort study. (3rd January 2019) - Goulden, R.; Whitehouse, T.; Murphy, N.; Hayton, T.; Khan, Z.; Shyamsundar, M.; Gao‐Smith, F.; Snelson, C.; Bion, J.; Veenith, T.
Summary: Higher mortality following admission to hospital at the weekend has been reported for several conditions. It is unclear whether this variation is due to differences in patients or their care. Status epilepticus mandates hospital admission and usually critical care: its study might provide new insights into the nature of any weekend effect. We studied 20, 922 adults admitted to UK critical care with status epilepticus from 2010 to 2015. We used multiple logistic regression to evaluate the association between weekend admission and in‐hospital mortality, comparing university hospitals with other hospitals. There were 2462 in‐hospital deaths (12%). There was no difference in mortality after weekend admission to university hospitals, adjusted odds ratio (95%CI) 0.99 (0.84–1.16), p = 0.89. Mortality was less after weekend admission than after admissions Monday to Friday in hospitals not associated with a university, adjusted odds ratio (95%CI) 0.74 (0.64–0.87), p = 0.0001. There is no evidence that adults admitted to UK critical care at the weekend in status epilepticus are more likely to die than similar patients admitted during the week.